HUKUM ISLAM TERHADAP PENGGUNAAN CRYPTOCURRENCY SEBAGAI ALAT PEMBAYARAN ZAKAT - Dewi, Shinta; Rodiah, Ita (Universitas Nurul Jadid, 2023)
ABSTRACTCryptocurrency has emerged as a significant phenomenon in the world of finance and technology. Along with its popularity, there have been debates and controversies regarding the use of cryptocurrency as a form of wealth and currency for zakat payment. Zakat in Islam os an obligation for every Muslim who financially capable, to give a portion of their wealth to those in need. However, the fluaction value of cryptocureency has sparked discussion on its feasibility for zakat payment. The objective of this paper is to explore the use of cryptocurrency as a means of zakat payment from the perspective of islamic law.Keywords : cryptocurrency, zakat, islamic law ABSTRAKCryptocurrency telah menjadi fenomena yang signifikan dalam dunia keuangan dan teknologi. Seiring dengan popularitasnya, muncul pro dan kontra terhadap penggunaan cryptocurrency sebagai harta dan mata uang yang dapat digunakan sebagai alat pembayaran zakat. Zakat dalam islam merupakan kewajiban bagi setiap muslim yang mampu memberikan sebagaian dari kekayaan kepada orang-orang yang membutuhkan. Namun, nilai cryptocurrrency yang fluaktif memicu perdebatan. Tujuan dalam makalah ini untuk mengetahui penggunaan cryptocurrency sebagai alat pembayaran dari sudut pandang hukum islam.Kata Kunci: cryptocurrency, zakat, hukum islam